Assessing the Safety of Ethnobotanical Remedies: An Allium cepa Root Tip Study on Four Medicinal Plant Extracts - Skaria, Chacko Suju; Rajappan, Rejitha Lalitha; Biju, Archana Sarah (Asian Journal of Biological and Life Sciences)
Aim: This study evaluated the cytotoxic and genotoxic potential of leaf extracts from four ethnobotanically significant plants (Trichopus zeylanicus, Naravelia alata, Cyclea peltata, and Smilax zeylanicus) using the Allium cepa root tip assay to assess their safety for medicinal use. Materials and Methods: Aqueous leaf extracts were prepared at concentrations of 25%, 50%, 75%, and 100%. Onion root tips were exposed to each extract for 1 hr, fixed in Carnoy’s fluid, hydrolyzed, and stained with acetocarmine for microscopic analysis. Mitotic Index (MI) and chromosomal aberrations were quantified to determine cytotoxicity and genotoxicity. Results: All extracts exhibited dose-dependent cytotoxicity, with MI decreasing significantly at higher concentrations. The 100% extract of S. zeylanicus showed the most severe suppression (MI=0.87%) and highest abnormality rate (99.1%). Chromosomal aberrations included stickiness, fragmentation, C-mitosis, bridge formation, and nuclear disintegration. T. zeylanicus and N. alata induced prominent stickiness and vacuolation, while C. peltata and S. zeylanicus caused spindle disturbances and clumping. Conclusion: The study confirms that these medicinal plants possess bioactive compounds with both therapeutic and genotoxic potential. The concentration-dependent effects highlight the need for careful dosage regulation in ethnomedicinal applications. Further phytochemical characterization is essential to isolate beneficial compounds while minimizing mutagenic risks.
Keywords: Allium cepa assay; cytotoxicity; Ethnobotany; Genotoxicity; Medicinal plants; Mitotic abnormalities.